The First Author of a Printed Book from Kaunas - Antanavičius, Darius (Senoji Lietuvos literatūra, 2018)
Very little is known about the contribution of the burghers of the Grand Duchyof Lithuania to old Lithuanian literature. The burghers were always pushedinto shadow by the representatives of the nobility. In this respect, the sixteenthcentury is especially poor and each new fact that adds to our knowledge aboutthe intellectual and creative potential of the townspeople of the Grand Duchyof Lithuania in the sixteenth century is significant. The aim of this paper is tointroduce and analyse a work written and published by one burgher of the GrandDuchy of Lithuania in the mid-sixteenth century.The object of research is a little-known rare publication the accurate full title of which is the following: Elegia de Re|surrectione Domini no|stri Iesu Christi, continens | descriptionem pugnae Ipsius apud inferos, |et simul triumphi Eius ascenden|tis ad Patrem, | scripta | ad illustrissimum prin|cipem et dominum, dominum Nicolaum Radziuil, | ducem in Olika et Niesuisz, palatinum Vilnensem, can|cellarium et marschalcum magni ducatus Lithuuaniae, | generalem Brestensem, Schanlensem, et | Borisoniensem capita|neum, etc. | autore Martino Grado|uuio Caunensi. L. | Anno 1561 [VD16 ZV 6919]. Only two copies of the Elegia are known to bibliographers during the 450 years that have passed since its publication. The fate of the copy described by Jan Daniel Janocki is unknown. In all likelihood it perished in the hardships of history that befell the Zaluski library. The only known copy, the so-called unicate, is currently kept in Germany, at the Gotha Research Library (Forschungsbibliothek Gotha). The shelfmark of the book: Phil. 4o 00203/05. It is a small eight-leaf publication in quarto, in a binding consisting of as many as 170 similar occasional works. The objectives of the article are the following: (1) to determine where precisely Elegia was printed, (2) to prove that the author of Elegia Martynas Gradovskis (Martinus Gradovius, Marcin Gradowski) was indeed a burgher of Kaunas, (3) to introduce his person and his family, and (4) to reveal a broader cultural and literary context of this small book.Since the place of publication is not given on the title page, all bibliographic sources claim that it is unknown. Although it is not given on the title page, it is not hard to identify from the dedication by Martynas Gradovskis, the author of Elegia, to Mikalojus Radvila the Black (Mikołaj Radziwiłł Czarny), the voivode of Vilnius. It turns out that the book was printed at the printing house of Johann Eichorn in Frankfurt (Oder).Not having seen the work itself and resorting to the reiterated title, the majority of those who wrote about Elegia had doubts as to whether Martynas Gradovskis was a burgher of Kaunas or possibly a noble. The above-mentioned dedication to Mikalojus Radvila the Black is a proof that Martynas Gradovskis, the author of Elegia, came from the burghers of Kaunas.So far only four undeniable facts are known about Martynas Gradovskis. First of all, his father Simonas Gradovskis was a burgher of Kaunas, a lay judge, member of Council, and eventually a burgomaster. Martynas must have been born in Kaunas. The exact year is unknown, but one can guess that he must have been born between 1540 and 1543. The second true fact is that in 1559 we see him at the University of Frankfurt (Oder): he enrolled during the spring term, after 23 April. The third fact is that Marcin stayed in Frankfurt (Oder) until 1561 (with or without intervals), and early in 1561 he wrote and published his Elegia here. On the title page, the author’s name is followed by the abbreviation L, which very likely means Licenciatus (-o), that is, the degree achieved. The fourth known fact is the date of his death. We know that he died early in 1569 in Gdansk. It becomes clear from the ascertained facts that Martynas Gradovskis died when he was 25–30 years old at the most; there was not enough time for self-realisation or an outstanding career, which explains why information about him in extant sources is scarce.More can be said about the family into which Martynas was born. His father, Simonas Gradovskis, was a burgher of Kaunas, a lay judge, member of Council, and eventually a burgomaster; his mother, Barbora Barčiūtė, was a townswoman. Simonas Gradovskis, a long-standing burgomaster of Kaunas, was one of the prominent personalities of Kaunas in the middle and the second half of the sixteenth century. He was born between 1510 and 1515, was a lay judge from at least 1544, later became member of Council, and a burgomaster in 1550. He died in the 1570s.Before 1561, numerous shorter or longer hymns and poems the main theme (object) of which was the underlying event of the Christian faith – the death and resurrection of Jesus Christ – appeared in Western Europe. Researchers in the field of Latin literature of the modern period mention Macario Muzio’s De triumpho Christi (1499), Iohannes Tuberinus’s Carmen elegiacum de Resurrectione Domini nostri Iesu Christi (1512), Sapphicon de inferorum vastatione et triumpho Christi (1512) by Paweł of Krosno (died in 1517), Eobanus Hessus’s (1488–1540) Victoria Christi ab inferis (1517) as first examples of this type of literature. Since there were more similar works and they started appearing like from a cornucopia in the middle and the second half of the sixteenth century, producing a register of them alone would be an immense work.The structure of Gradovskis’ Elegia is typical of this kind of plot: Jesus’s descent into the world of the dead, the struggle against the forces of the underworld and their defeat or a victory over death, and a triumphal procession to heaven. The interlacing rhetoric speeches occur in various combinations in all similar works. Regarding the authors that Martynas Gradovskis resorted to, mention should be made of Veit Jacobaeus. He was born in Nuremberg, but the year of his birth is unknown. He taught poetics at the University of Vienna and in 1558 was crowned poeta laureatus. In 1561 he left Vienna for Ingolstadt where in 1562 he received professorship in poetics. Jacobaeus died in 1568. There is no doubt that Martynas Gradovskis knew Jacobaeus’s hymn about Christ’s resurrection, which was first published in Vienna in 1555 under the title Triumphus gloriosissimus Filii Dei ascendentis ad dexteram Aeterni Patris [VD16 J 58], reprinted in Wittenberg in 1556 as Triumphus Filii Dei ascendentis ad Patrem [VD16 ZV 8625], and eventually was included in the first volume of the collection ‘Holy Hymns’ (Carmina sacra) published in 1561 in Vienna [VD16 J 55]. Martynas Gradovskis must have used one of these editions.A number of lines from Jacobaeus’s work found their way to the above-mentioned dedication to Mikalojus Radvila the Black. Even more ‘impressive’ are the borrowings from Jacobaeus in the main body of the text of Elegia. We identified as many as 112 lines that had been taken from the hymn by this author either verbatim or with slight stylistic changes. With insignificant exceptions, Elegia’s whole second part about Christ’s ascension to heaven is basically copied from Jacobaeus’s work. Due to their large volume, these episodes are given in the appendix. How should such a fact be accounted for? It substantially changes our opinion of Martynas Gradovskis and his work. What initially might have appeared as a manifestation of a considerable talent turns out to be a simple imitation that had been learned while studying the humanities at the schools of that time. The fact that Martynas Gradovskis used, in one way or another, and very often simply copied 125 lines of the 286 lines of Jacobaeus’s hymn makes us speak not about some sophisticated kind of imitation but about what is called plagiarism in our times.
Keywords: Christoph Caesar; Johann Eichorn; elegy; Frankfurt (Oder); Martynas Gradovskis (Marcin Gradowski, Martinus Gradovius); Simonas Gradovskis (Szymon Gradowski); Veit Jacobaeus (Jakobäus); Kaunas; 16th century; Kaspar Langerfeld; Grand Duchy of Lithuania; Latin literature of Lithuania; history of Reformation in Lithuania; Macario Muzio; modern period; Georg Pictorius; Mikalojus Radvilas the Black (Mikołaj Radziwiłł Czarny)